A Cost-Effective Solid-State Approach to Synthesize g-C3N4 Coated TiO2 Nanocomposites with Enhanced Visible Light Photocatalytic Activity. (26th September 2013) - Fu, Min; Pi, Junmin; Dong, Fan; Duan, Qiuyan; Guo, Huan
Abstract : Novel graphitic carbon nitride (g-C3 N4 ) coated TiO2 nanocomposites were prepared by a facile and cost-effective solid-state method by thermal treatment of the mixture of urea and commercial TiO2 . Because the C3 N4 was dispersed and coated on the TiO2 nanoparticles, the as-prepared g-C3 N4 /TiO2 nanocomposites showed enhanced absorption and photocatalytic properties in visible light region. The as-prepared g-C3 N4 coated TiO2 nanocomposites under 450°C exhibited efficient visible light photocatalytic activity for degradation of aqueous MB due to the increased visible light absorption and enhanced MB adsorption. The g-C3 N4 coated TiO2 nanocomposites would have wide applications in both environmental remediation and solar energy conversion.